2020
DOI: 10.7150/thno.52135
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D3 controls mouse and human TRPV1-positive neurons and preclinical progression of psoriasis

Abstract: Rationale: Psoriasis is a chronic inflammatory disease caused by a complex interplay between the immune and nervous systems with recurrent scaly skin plaques, thickened stratum corneum, infiltration and activation of inflammatory cells, and itch. Despite an increasing availability of immune therapies, they often have adverse effects, high costs, and dissociated effects on inflammation and itch. Activation of sensory neurons innervating the skin and TRPV1 (transient receptor potential vanilloid 1) ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 80 publications
(119 reference statements)
2
38
0
Order By: Relevance
“…Other authors suggested disturbances in the endogenous opioid system homeostasis, but there is still no final proof that indeed the observed abnormalities are a primary phenomenon in psoriasis leading to pruritus [ 41 , 42 ]. Recent data also indicated the role of transient receptor potential (TRP) channels, such as TRPV1, TRPV4, or TRPM8, but further studies are needed to confirm their relevance [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors suggested disturbances in the endogenous opioid system homeostasis, but there is still no final proof that indeed the observed abnormalities are a primary phenomenon in psoriasis leading to pruritus [ 41 , 42 ]. Recent data also indicated the role of transient receptor potential (TRP) channels, such as TRPV1, TRPV4, or TRPM8, but further studies are needed to confirm their relevance [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has revealed that TRPs are actively involved in the regulation of skin physiology [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. TRPV1 expression has been identified in epidermal and hair follicle keratinocytes, dermal mast cells, sebaceous gland-derived sebocytes, and dendritic cells [ 78 , 79 ], which suggest functional roles in homeostatic and ‘sensory’ functions not limited to cutaneous nerve fibers.…”
Section: Trpa1 In Skin Physiologymentioning
confidence: 99%
“…RvD2 (10 ng, 100 ng) or vehicle (2% ethanol in PBS) was injected intrathecally as described in previous studies. 18,19 Before using O-1918, the methyl acetate was evaporated under a gentle stream of nitrogen, and vehicle was immediately added. The final concentration of O-1918 was 25 mM.…”
Section: Drug Administrationmentioning
confidence: 99%